A novel design of Butler matrix using optimised size of branch-line coupler - Rahim, S.K.A.; Jizat, N.M.; Rahman, T.A.; Geok, T.K.; Reza, A.W. (INOE Publishing House, 2010)
Recent development shows that the reduced size couplers are becoming potential building blocks for the growing wireless communications market. This paper presents a new design and realisation of four ports Butler Matrix using the reduced size of branch-line coupler operating at 1.8GHz. The purpose is to reduce the size of branch-line coupler to agree with the application requirements, e.g., mobile applications. Butler Matrix generally consists of branch-line coupler, crossover, and phase shifters. The branch-line coupler has been used as the functional and smart component in constructing the planar of 4x4 Butler Matrix. Using the two-step stubs impedance, the size of the branch-line coupler is optimised in this study. The obtained results show that the area of branch-line coupler has been reduced to 66% compared to the normal size branch-line coupler. Besides, the reduced size coupler shows the same performance like the normal coupler, maintains lower manufacturing cost and miniaturisation in size. The results obtained from this study show satisfactory performance and good agreement with the theoretical results.